PENGEMBANGAN HIDROPONIK SEBAGAI SARANA HULU KEMANDIRIAN PANGAN BERBASIS PEMBERDAYAAN EKONOMI DI KAMPUNG PUGERAN KELURAHAN SURYODININGRATAN KECAMATAN MANTRIJERON, KOTA YOGYAKARTA - Nakuloadi, Hening (PRIMA EKONOMIKA, 2019)
Technological developments in the field of agriculture are increasinglyrapidly increasing, so that communities, especially farmers who are lagging behindin utilizing technological advances, will not get the maximum benefit from thebusiness activities they do. One of the technologies that deserves to be disseminatedis hydroponic technology, this is because the scarcity of agricultural land is due tothe large number of industrial and service sectors, so conventional agriculturalbusiness activities are increasingly not competitive due to the high price of land. The technology of agricultural cultivation with a hydroponic system isexpected to be an alternative for people who have limited land or yard, so that itcan be used as an adequate source of income. Hydroponics is a method of farmingusing planting media other than soil, such as pumice, gravel, sand, coconut fiber,pieces of wood or you can. This is done because the function of the soil as a supportfor plant roots and intermediate nutrient solutions can be replaced by flowing oradding nutrients, water and oxygen through the media